Peanut Rotation and Flooding Induce Rhizobacteriome Variation With Opposing Influences on the Growth and Medicinal Yield of Corydalis yanhusuo - Li, Xiaodan; Wang, Songfeng; Fan, Yating; Zhou, Zhe; Xu, Sheng; Zhou, Penglei; Zhou, Jiayu; Wang, Ren (Frontiers in Plant Science, 2022)
Corydalis yanhusuo, a precious herb of the Papaveraceae family, is widely used in multiple traditional Chinese medicines for the treatment of many painful conditions, and its medicinal part is the dried tuber. Yet how to improve this plant’s medicinal yield as well as its economic efficiency remains a key problem in its cultivation. The planting of C. yanhusuo in rotation with peanut (Arachis hypogaea L.) aims to improve land utilization efficiency, but the total production of tubers is severely reduced relative to fields without rotation. However, an increased yield was observed in C. yanhusuo plants grown in previously flooded fields (HR field) compared to the ones grown in the fields that had been used to cultivate peanut (PL field) or in fields without rotation or flooding (N field). Based on these phenomena, in this study, we explored the potential factors responsible for the altered growth/yield of C. yanhusuo under different field conditions. Soil physicochemical properties and the diversity and community of rhizobacteriome of C. yanhusuo were both analyzed. By testing several soil physicochemical properties, we found that the cation exchange capacity (CEC), soil organic matter (SOM), total nitrogen (TN), and pH value differed significantly among these three types of fields. 16S rRNA amplicon sequencing revealed stark differences in the composition, diversity, and potential functions of the bacterial community in the rhizosphere of C. yanhusuo plants grown in field with the peanut rotation or flooding. Notably, the Acidobacteria were enriched in the HR field, while Actinobacteria were enriched in the PL field. More importantly, further analysis showed that changed soil physicochemical properties could be one reason for why the rhizospheric bacterial community has changed; hence, soil physicochemical properties might also be affecting plant performance indirectly by regulating the rhizospheric bacterial community. The RDA analysis distinguished CEC as the most important soil physicochemical property influencing the structure and composition of the C. yanhusuo rhizobacteriome. In summary, our results suggest peanut rotation- and flooding-induced soil physicochemical properties changes would further impact the rhizobacteriome of C. yanhusuo albeit differentially, culminating in opposite effects upon the plant growth and medicinal yield of C. yanhusuo.